Knowledge Level of Synthetic Cough Medicine Self-Medication and List of Traditional Medicines Used by the Insignia Oasis Housing Society - Sulfiyana H. Ambo Lau; Gerfan Patandung; Marselinus Kaka (Politeknik Sandi Karsa, 2023)
Coughing is a natural response by increasing the clearance of mucus secretions and particles, irritants, foreign particles, and microbes, so that it becomes the body's defense mechanism. Self-medication practitioners must know about synthetic drugs and traditional medicines used to treat coughs. This study aims to determine the level of self-medication knowledge of synthetic cough medicines and a list of traditional medicines used by the Insignia Oasis housing community which will be held in March 2023 at Insignia Oasis Housing. The type of research used is descriptive observational research using a questionnaire to obtain data with a total of 56 respondents. The results of this study indicate that the percentage of respondents' answers is 89.91%. Based on these results it can be concluded that the level of self-medication knowledge of synthetic cough medicine and the list of traditional medicines used by the Insignia Oasis housing community is in the high category and uses ginger the most.